The Investment Urgency In Ultra Micro Organizational Going Concern - Rohma, Frida Fanani; Syahputra, Bagus Erlangga (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2022)
This study aims to explore and examine the role of investment in encouraging the sustainability of micro-enterprises. This research was conducted using a qualitative method in one of the ultra micro businesses engaged in manufacturing in the food and beverage industry. The results showed that the